2015
DOI: 10.1111/ppa.12368
|View full text |Cite
|
Sign up to set email alerts
|

Foliar terpenoid levels and corresponding gene expression are systemically and differentially induced in Eucalyptus grandis clonal genotypes in response to Chrysoporthe austroafricana challenge

Abstract: Induction of systemic defences to fungal pathogens is well described in model plant systems, but not extensively studied in large woody perennials. Systemic induced defences in long‐lived tree species, such as Eucalyptus grandis, could provide resistance against subsequent biotic challenges. Terpenoids are a class of plant‐specialized metabolites implicated in defence against herbivores and pathogens. The aim of this study was to characterize the systemic induction of terpenoids in E. grandis clones challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Induction of TPS genes or changes of terpene concentrations in response to biotic and abiotic stress has rarely been shown in Myrtaceae (Webb et al, 2014 ). Apart from a recent study where some TPS ‐encoding genes and terpenes were observed to be upregulated in E. grandis upon challenge by Leptocybe invasa (gall wasp; Oates et al, 2015 ) and another study which found induced expression of isoprene synthase‐ and β‐caryophyllene synthase‐encoding genes ( EgrTPS084 and EgrTPS038 , respectively) in E. grandis in response to C. austroafricana infection (Visser et al, 2015 ), there has been little to no evidence of induction of terpenes in Eucalyptus or Melaleuca in response to wounding, herbivory, or even application of methyl jasmonate (MeJA; Henery et al, 2008 ). Henery et al ( 2008 ) noted that it was possible that herbivory and MeJA could still induce TPS genes in Eucalyptus without increasing the amount of constitutive terpenes contained in the leaves due to volatile losses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of TPS genes or changes of terpene concentrations in response to biotic and abiotic stress has rarely been shown in Myrtaceae (Webb et al, 2014 ). Apart from a recent study where some TPS ‐encoding genes and terpenes were observed to be upregulated in E. grandis upon challenge by Leptocybe invasa (gall wasp; Oates et al, 2015 ) and another study which found induced expression of isoprene synthase‐ and β‐caryophyllene synthase‐encoding genes ( EgrTPS084 and EgrTPS038 , respectively) in E. grandis in response to C. austroafricana infection (Visser et al, 2015 ), there has been little to no evidence of induction of terpenes in Eucalyptus or Melaleuca in response to wounding, herbivory, or even application of methyl jasmonate (MeJA; Henery et al, 2008 ). Henery et al ( 2008 ) noted that it was possible that herbivory and MeJA could still induce TPS genes in Eucalyptus without increasing the amount of constitutive terpenes contained in the leaves due to volatile losses.…”
Section: Discussionmentioning
confidence: 99%
“…Other than studies that investigated the effects of terpenes to beetle‐vectored fungal defense in several conifer species (Keeling & Bohlmann, 2006 ; Zeneli et al, 2006 ), only few studies investigated induced terpenes with potential antifungal properties in plants in response to fungal infections alone. For example, Visser et al ( 2015 ) compared gene expression profiles between resistant and susceptible Eucalyptus grandis in response to the necrotrophic fungus Chrysoporthe austroafricana and identified inductions of transcripts encoding a putative isoprene synthase ( EgrTPS084 ) and a β‐caryophyllene synthase ( EgrTPS038 ) after infection in resistant plants. Maize ( Zea mays ) responds to infection by Fusarium graminearum by producing zealexins and kauralexins (both terpenoids) in response to Cercospora zeina (Huffaker et al, 2011 ; Meyer et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, improving trees for resistance to combined biotic and abiotic stresses using these techniques may also become possible. Existing model systems that have been used to study biotic stresses such as those in Eucalyptus (Naidoo et al, 2013;Mangwanda et al, 2015;Visser et al, 2015), Pine (Visser et al, 2018), and Poplar (Feau et al, 2007;Hacquard et al, 2011) can be used to develop a workable approach in this regard. We propose the use of drought-pathogen interactions, which has been considered a model in annual crops (Pandey et al, 2017), to study combined biotic and abiotic stresses in forest trees.…”
Section: Mitigation Strategiesmentioning
confidence: 99%